Teachers' Readiness for Implementing the Merdeka Curriculum in English Instruction - Tohamba, Citra Prasiska Puspita; Ansyar, Muhammad (Contemporary Education and Community Engagement (CECE), 2025)
Curriculum changes are a common strategy to enhance the quality of education. The transition from the 2013 Curriculum to the Merdeka Curriculum requires teachers to be adequately prepared to comprehend changes in content, structure, planning, implementation, and evaluation of the new curriculum, particularly in the 2023-2024 academic year. This study aims to assess the readiness of teachers in implementing the Merdeka Curriculum for English instruction in elementary schools. A qualitative case study approach was employed, focusing on grade 1 and grade 4 teachers who have implemented the curriculum. Data collection methods included interviews, observations, and document analysis. The data analysis process followed three stages: data reduction, data display, and conclusion drawing/verification. The findings reveal that teachers demonstrate readiness in implementing the Merdeka Curriculum, preparing lesson plans, and adapting to its new elements. Despite the introduction of new terms and curriculum structures, teachers are utilizing online resources and textbooks as primary teaching aids. However, challenges persist, particularly as English is now a core subject, and many teachers lack formal training in English language education. Additionally, while formative and summative assessments have been incorporated, diagnostic assessments at the beginning of the learning process remain underutilized, limiting teachers’ ability to assess students' prior knowledge and learning gaps. This study contributes to policy development and teacher training by highlighting the need for targeted professional development programs, particularly in English language education, and suggesting the importance of incorporating diagnostic assessments to better address students' learning needs from the outset.